ANALYSIS EFFECT OF WORK ENVIRONMENT AND FLEXIBLE WORKING TOWARD EMPLOYEE RETENTION FOR INDONESIANS MILLENNIAL THROUGH CAREER DEVELOPMENT AS INTERVENING VARIABLE - Septiani, Dian Ayu (International Humanities and Applied Science Journal, 2021)
Millennial is indeed synonymous with high employee turnover rates. This research is to performed employee retention for Indonesians millennials through the work environment, career development, and flexible working to give an overview and additional source of information for the organization to be able to manage their employees who are in the millennial generation to keep them stay longer in the workplace and reduce turnover rate among Indonesians millennials employee. Data analysis method in this research is using SPSS program for the Descriptive Statistic and also using PLS program (Partial Least Square) Version 3.0 for calculating the Outer Model and Inner Model. The populations are a millennial employee in Indonesia and the number of populations is unknown, so the sample in this research are 140 respondents. The results of this research can generally be concluded that Work Environment and Flexible Working have a positive and significant effect on Employee Retention. As well as Career Development can be mediation between Work Environment and Flexible Working toward Employee Retention.Keywords: Work Environment, Career Development, Flexible Working, Employee Retention, Indonesians Millennial